P.K. Feyerabend, Explanation, Reduction and Empiricism - José Alberto Coffa (Crítica)
P.K. Feyerabend, "Explanation, Reduction and Empiricism", Minnesota Studies in the Philosophy of Science, University of Minnesota Press, 1962, pp. 28-97.